DTN Trustworthiness for Permafrost Telemetry IoT Network - Adrià Mallorquí (MDPI AG, 2021)
The SHETLAND-NET research project aims to build an Internet of Things (IoT) telemetry service in Antarctica to automatize the data collection of permafrost research studies on interconnecting remote wireless sensor networks (WSNs) through near vertical incidence skywave (NVIS) long fat networks (LFN). The proposed architecture presents some properties from challenging networks that require the use of delay tolerant networking (DTN) opportunistic techniques that send the collected data during the night as a bulk data transfer whenever a link comes available. This process might result in network congestion and packet loss. This is a complex architecture that demands a thorough assessment of the solution’s viability and an analysis of the transport protocols in order to find the option which best suits the use case to achieve superior trustworthiness in network congestion situations. A heterogeneous layer-based model is used to measure and improve the trustworthiness of the service. The scenario and different transport protocols are modeled to be compared, and the system’s trustworthiness is assessed through simulations.